Access to Credit among Micro, Small, and Medium Enterprises - Alper, Oya; Hommes, Martin (International Finance Corporation, Washington, DC, 2015)
In 2010, IFC conducted a study to estimate the number of micro, small, and medium enterprises (MSMEs) in the world, and to determine the degree of access to credit and use of deposit accounts for formal and informal MSMEs. The study used primarily data from the World Bank Enterprise Surveys (ES). In 2011 the data was revisited as new enterprise surveys became available. The resulting database, IFC Enterprise Finance Gap Database, covers 177 countries. This fact sheet summarizes and highlights the key data points available for the formal micro, formal small and medium enterprises (SME), and the aggregated formal and informal MSME sectors.